2016
DOI: 10.1186/s13570-016-0053-1
|View full text |Cite
|
Sign up to set email alerts
|

Value chain analysis of grass seeds in the drylands of Baringo County, Kenya: A producers’ perspective

Abstract: Pastoral households are increasingly practising fodder production in response to forage scarcity associated with land degradation, climate variability and change. Understanding the grass seed value chain is a prerequisite for developing sustainable fodder production and guiding appropriate out-scaling in the drylands. This study investigated the producers' perspectives on grass seed production, marketing and challenges faced along the grass seed value chain in Marigat SubCounty of Baringo County, Kenya. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
3
19
0
Order By: Relevance
“…Therefore, it is only rational for the pastoralists to learn from these experiences, buy and store fodder in preparedness for drought seasons to mitigate losses. These finding corroborates Lugusa et al (2016) who observed that pastoral households who had experience with droughts were more likely to join fodder groups to easily access livestock feeds.…”
Section: Factors Influencing Pastoralists' Participation and Intensity Of Participation In Fodder Marketssupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, it is only rational for the pastoralists to learn from these experiences, buy and store fodder in preparedness for drought seasons to mitigate losses. These finding corroborates Lugusa et al (2016) who observed that pastoral households who had experience with droughts were more likely to join fodder groups to easily access livestock feeds.…”
Section: Factors Influencing Pastoralists' Participation and Intensity Of Participation In Fodder Marketssupporting
confidence: 90%
“…In Baringo County, the grass seed market is formalized, as transactions are based on contractual arrangements that integrate input provision and purchase of seeds. This is due to the involvement of large private sector players such as the Kerio Valley Development Authority (KVDA), Rehabilitation of Arid Environments Trust (RAE) and Kenya Agricultural and Livestock Research Organization (KALRO) (Lugusa et al 2016). Omollo et al (2017) noted that grass seed markets in Kajiado and Makueni Counties are still developing and informal in nature with limited private sector participation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was because some of the ephemerals like S. verticillata were present only during the wet season. Ephemerals are grass species which regenerate immediately after the rains (Verdoodt et al 2010;Lugusa et al 2016), emerging where decreaser species have been depleted as a result of heavy grazing and are therefore a sign of poor range condition (Oluwole Sabiiti and Teka (2004) and Machogu (2013), Chloris, Hyparrhenia, Aristida, and Sporobolus spp. are some of the most pronounced grasses in the East African rangelands due to their selfseeding ability, tolerance to drought, and spreading capacity.…”
Section: Species Compositionmentioning
confidence: 99%
“…With climate change and the associated higher variability of the beginning and duration of the various seasons, grass is considered a more secure crop compared to local staple crops like maize or beans; particularly perennial grass species require less rain for completion of a cropping cycle. Growing grass for seed production is widespread in some of the sublocations, and farmers can also sell the hay (Lugusa et al, 2016). Pressure on grazing land is generally very high in Baringo and other pastoralist regions in Eastern Africa, with overgrazing having contributed considerably to land degradation and an increase in bare areas (Kiage et al, 2007).…”
Section: Financial and Immaterials Benefits Of Restoring Grasslandsmentioning
confidence: 99%